Neoadjuvant chemotherapy impacts axillary lymph node positivity in early breast cancer (cT1-2N0M0) with negative axillary lymph nodes at diagnosis - Ma, Jinxiu; Fan, Zhimin; Jia, Zhifang; Dong, Xiaoxiao; Sun, Jian; Wang, Xiaozhen (Frontiers in Medicine, 2025)
PurposeThis study compared the role of neoadjuvant chemotherapy (NAC) followed by surgery vs. upfront surgery for avoiding axillary lymph node dissection (ALND) in patients with cT1-2N0M0 breast cancer and clinically negative axillary lymph nodes (LNs) at diagnosis.Patients and methodsMedical records of a sample of 1,695 patients with a primary diagnosis of axillary LN-negative early-stage breast cancer who underwent surgical treatment for breast cancer at the First Bethune Hospital of Jilin University between June 2019 and December 2022 were retrospectively reviewed. The positive rate of sentinel lymph nodes (PRSLN) and the positive rate of total axillary lymph nodes (PRTLN) were compared between patients who received 4–8 cycles of NAC followed by surgery (n = 135) and patients who underwent upfront surgery (n = 1,560).Results15 patients who received NAC followed by surgery and 79 patients who underwent upfront surgery had positive SLNs. Four patients who received NAC followed by surgery and 1 patient who underwent upfront surgery had other positive LNs. Overall, NAC followed by surgery significantly lowered PRSLN and PRTLN compared to upfront surgery in patients with cT1-2N0M0 breast cancer. In subgroup analyses, PRSLN and PRTLN were significantly lower for NAC followed by surgery compared to upfront surgery in patients aged 40–60 years, with cT2 stage disease, and HER2+ breast cancer. At a median follow-up of 23.15 months, invasive disease-free survival was similar for all patients.ConclusionNAC may reduce the rate of axillary LN positivity and the likelihood of ALND in patients aged 40–60 years with cT2N0M0 HER2+ breast cancer and clinically negative axillary LNs at diagnosis.